Alienation and Nostalgia in Immigrant Literature in Jhumpa Lahiri's Novel “Namesake” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The current research paper explores the feelings of profound alienation and nostalgia common to immigrant literature. It aims to explore the path traversed by people who abandon their nations to embrace new but unfamiliar cultural norms, language barriers, and an overall sense of rooted alienation. Overall, the study proposes to define and develop concepts of alienation and nostalgia in immigrant literature, understand what triggers these feelings and how they are expressed, and reflect on literature's role in healing them.Alienation as an emotion of separation and dissociation from oneself and people around are depicted. It is analyzed by sociologists, philosophers, and psychologists who present the sociological, economic, and psychological approaches to understanding the phenomenon. Moreover, the paper also reflects the second type of alienation of people from their house and their motherland, which illustrates the challenges of immigrants in a new social and cultural environment. Nostalgia, therefore, is researched as a feeling of homesickness and longing for their motherland and their previous life. It is a remembrance of past and time-preserved identity.In summary, this research paper contributes unique perspectives to the themes of alienation and nostalgia in immigrant-based literature. The research paper enriches different aspects of these feelings, their origins, and manifestations, bearing in mind that literature plays a crucial role from which psychological impacts of alienation and nostalgia should not escape. Such a view is only insightful in ensuring how the feeling of alienation and nostalgia influences the immigrant and their fight to develop a complete identity.